VD_FINDINFO HC / 2013 / 196 vom 21. März 2013 - VD Tribunal cantonal (2013)
MESURE PROVISIONNELLE, DROIT BANCAIRE, CRÉDIT LOMBARD, NANTISSEMENT, RÉSILIATION, JUSTE MOTIF, PREUVE FACILITÉE, PACTE COMMISSOIRE | 261 CPC (CH)